Remarkable static and dynamic NLO response of alkali and superalkali doped macrocyclic [hexa-]thiophene complexes; a DFT approach. Issue 7 (20th January 2021) - Sajid, Hasnain; Ullah, Faizan; Khan, Sidra; Ayub, Khurshid; Arshad, Muhammad; Mahmood, Tariq
Abstract : In this study, the nonlinear optical (NLO) response of alkali metal atom (Li, Na and K) and their corresponding superalkali (Li3 O, Na3 O and K3 O) doped six membered cyclic thiophene (6CT) has been explored. Abstract : In this study, the nonlinear optical (NLO) response of alkali metal atom (Li, Na and K) and their corresponding superalkali (Li3 O, Na3 O and K3 O) doped six membered cyclic thiophene (6CT) has been explored. The optimized geometries of complexes; Li@6CT, Na@6CT, K@6CT, Li3 O@6CT, Na3 O@6CT and K3 O@6CT depict that the superalkalis and alkali metals interact through the active cavity of 6CT. Interaction energies reveal that superalkalis have higher interaction with 6CT than alkali metals. The nonlinear optical (NLO) response of the reported complexes is estimated via both static and dynamic hyperpolarizabilities which are further rationalized by the HOMO–LUMO gap, natural bond orbital (NBO) charge transfer, dipole moment, polarizabilities and β vec . A remarkably high NLO response is computed for Na3 O@6CT among all of the complexes. The static hyperpolarizability of the Na3 O@6CT complex is 5 × 10 4 au along with the highest β vec value (2.5 × 10 4 au). High charge transfer (1.53 e − ) and small E H–L gap (2.96 eV) is responsible for such a large NLO response. For dynamic NLO responses, electro-optic Pockel's effect (EOPE) and second-harmonic generation (SHG) are explored. A very large quadratic nonlinear optical response (3.8 × 10 −12 au) is observed for the Na3 O@6CT complex. Moreover, the absorption spectrum of the Na3 O@6CT complex shows ultra-high transparency in the ultraviolet and visible regions unlike any other of its counterparts.